Facial Nerve Considerations for the Deep Plane Facelift and Neck Lift - Azizzadeh, Babak; Lu, Richard J. (Facial Plastic Surgery, 2024)
The surgical approach to facial rejuvenation has evolved significantly over the last century. As surgeons have deepened their understanding of facial anatomy over the last half century, so have their surgical approaches to the rhytidectomy, with increasingly extensive manipulation of the underlying soft tissue in the face. While these procedures have become more comprehensive and natural in their approach, the risk of temporary facial palsy also appears to be on the rise. In this text, we review the technique for deep plane facelifts and neck contouring with an emphasis on the facial nerve anatomy and methods to preserve the intricate facial nerve network during tissue dissection and modification. Careful execution of the surgical steps involved, including deep neck contouring, SMAS (superficial musculoaponeurotic system) suspension, and skin management, is essential to achieve the authentic aesthetic outcomes that patients desire while ensuring patient safety.
Keywords: deep plane facelift; rhytidectomy; facelift; neck lift; facial nerve